What Shapes Environmental Responsibility Perceptions? Measuring Value Orientations as a Predictor of Situational Motivations and Communicative Action. Issue 3 (27th May 2019) - Li, Jo-Yun; Kim, Joon Kyoung; Overton, Holly; Bhalla, Nandini; Zhang, Nanlan; Choi, Minhee; Moon, Won-Ki
ABSTRACT: This study investigates individuals' cognitive, motivational, and communication responses regarding an environmental CSR issue using arguments from the situational theory of problem-solving (STOPS) with a cross-situational factor as an antecedent. Survey results provide empirical support for the application of the STOPS in a CSR communication context and suggest that a collectivistic orientation predicts individuals' situational perceptions and cognitive reactions toward organizations' environmental CSR efforts. Theoretical and practical implications for strategic communicators are discussed.